2001
DOI: 10.1200/jco.2001.19.2.464
|View full text |Cite
|
Sign up to set email alerts
|

Solid Cancers After Bone Marrow Transplantation

Abstract: The risk of radiation-associated solid tumor development after BMT is likely to increase with longer follow-up. This underscores the importance of close monitoring of patients who undergo BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
227
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(243 citation statements)
references
References 26 publications
10
227
2
1
Order By: Relevance
“…Because these practices are relatively new, their impact on risk for SN is poorly understood. Most studies have shown no association, 22,36,38,41 but they are generally small with limited follow-up.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because these practices are relatively new, their impact on risk for SN is poorly understood. Most studies have shown no association, 22,36,38,41 but they are generally small with limited follow-up.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
“…62 In contrast, two other studies found no association between pre-HCT chemotherapy and risk of SN. 41,62 Pre-HCT radiotherapy has been shown to be an adverse risk factor for SN. 59,60,62 Among 133 patients with aplastic anemia undergoing allogeneic HCT, pre-HCT immunosuppressive therapy with cyclosporine (a group 1 carcinogen according to the International Agency for Research on Cancer) 124 was associated with five-fold higher rates of SN.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A predilection to prostate malignancy was reported by multiple authors. Whereas, of the six secondary malignancies amongst 392 CML patients reported by Bhatia et al [19], none affected prostate (all had either cervical or oral cancers). Study from animal models have shown increased frequency of malignancies of parathyroid, stomach, adrenal, renal and urinary system in rats who received imatinib of 60 mg/kg/day [20].…”
Section: Secondary Malignancies In Cml: Pre-imatinib Eramentioning
confidence: 84%
“…Authors have reported secondary malignancies with predilection to specific organs/body sites, particularly head/neck, cervical and prostate [15,19,23]. This site predilection would be influenced by various other factors including regional prevalence, eating habits, smoking behaviour, physician reporting etc.…”
Section: Secondary Malignancies In Tki Treated CMLmentioning
confidence: 99%